2020
DOI: 10.3390/jcm9061989
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Rotary, Reciprocating, and Combined Non-Surgical Endodontic Retreatment Techniques in Removing a Carrier-Based Root Canal Filling Material from Straight Root Canal Systems: A Micro-Computed Tomography Analysis

Abstract: The aim of this study is to analyze and compare the efficacy of three non-surgical endodontic retreatment techniques in removing a carrier-based root canal filling material from straight root canal systems. The study was performed on 99 single-rooted extracted teeth using the ProTaper Gold endodontic rotary system up to the F2 file (Dentsply Maillefer, Baillagues, Switzerland), which were sealed with GuttaCore (Dentsply Maillefer, Ballaigues, Switzerland) and AH plus epoxy resin sealer (Dentsply DeTrey, Konsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…In the present study, the results showed that an increase to the next instrument size (tip size 30 to 40) might not directly correspond to a decrease in residual obturation material volume. Different methodologies, tooth types, instrument sizes, and motions can influence the shaping ability of the instruments [ 1 , 4 , 6 , 29 , 30 , 31 , 32 ]. Even though the number of unprepared areas was shown to be inversely proportional to the increase of each preparation size, a consequent thinner remaining dentin can compromise the tooth’s survival [ 11 , 28 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the results showed that an increase to the next instrument size (tip size 30 to 40) might not directly correspond to a decrease in residual obturation material volume. Different methodologies, tooth types, instrument sizes, and motions can influence the shaping ability of the instruments [ 1 , 4 , 6 , 29 , 30 , 31 , 32 ]. Even though the number of unprepared areas was shown to be inversely proportional to the increase of each preparation size, a consequent thinner remaining dentin can compromise the tooth’s survival [ 11 , 28 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical endodontic retreatment is challenging and, although there have been advancements in instrumentation technology, the predictability of filling material removal is still low. Strategies for cleaning and disinfection will essentially depend on either supplementary approaches or enlargement to even larger sizes [ 1 , 2 , 3 , 4 ]. Adjunctive procedures show controversial outcomes and still do not enable the thorough cleaning of root canals [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…NiTi retreatment files have no advantages over conventional techniques. Reciprocating and rotary systems exhibit similar capabilities in removing root filling material [13] . When used in the initial penetration stage, solvents can improve the root canal penetration of the files, but can make cleaning difficult and, if used after instrumentation, can reduce residual filling material [14] .…”
Section: Non-surgical Re-treatmentmentioning
confidence: 99%
“…Additional agitation of intra-canals' irrigants by laser irradation, sonic or ultrasonic vibrations has been reported to significantly improve removal of fillings materials [13][14][15]. Reciprocating systems have also shown good results [8,[16][17][18][19]. Madarati et al found that reciprocating instruments were better than rotary instruments in removing root canals fillings [16].…”
Section: Introductionmentioning
confidence: 99%